Leadership change: a case study analysis of strategy and control systems development - Alauddin, Ahmadasri; Abdullah, Zarifah; Ibrahim, Marhaiza (2017)
This paper reports on how a change of leadership at the CEO-level influences strategic practices and control systems development.The case study describes how the new chief executive developed and communicated his vision and strategy through control systems and structural change.The findings indicate that senior employees’ involvement in strategic plan development (through SLT mechanism in this case) brought clarity and assurance to them.Meetings are important control mechanisms to structure the sharing of information and to enhance employee commitment and help decision making.It is argued leadership manifests through the interactions of leader with employees in many control practices.The findings have implications for family-owned businesses that are facing imminent change in leadership.They benefit founders/top managers that are about to change leadership of entrepreneurial firm to the next level by highlighting the importance of preparing leader’s capacity for an effective leadership role.The study also highlights some important factors which are seldom discussed in control theories.